Awakening Uniqueness: Branding Strategy of Undisan Rural Tourism in Bangli Regency Through Eco-Experience - Maheswari, A.A. Istri Agung; Gorda, Anak Agung Ngurah Oka Suryadinatha; Parasari, Nyoman Sri Manik; Pradhana, I Putu Dharmawan; Anggreswari, Ni Putu Yunita (E-Journal of Tourism; Volume 10 Number 2 (September 2023)DO - 10.24922/eot.v10i2.107891, 2023)
This research article explores the branding strategy of Undisan Rural Tourism in Bangli Regency, with a focus on its success in winning the 3rd Places of Tourism Village Award through an eco-experience. The study utilizes a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis to identify and evaluate key factors that contribute to the village's branding strategy. Undisan Rural Tourism embodies a unique blend of natural beauty, cultural heritage, and sustainable practices, making it an exemplary case study for rural tourism development. The research methodology involves qualitative approaches. Primary data is collected through interviews, surveys, and participant observations, while secondary data is gathered from relevant literature, reports, and online sources. The SWOT analysis framework is applied to assess the internal and external factors that influence the branding strategy of Undisan Rural Tourism. The findings of the study reveal several strengths that have contributed to the success of Undisan Rural Tourism. These include its pristine environment, rich cultural heritage, authentic local experiences, and strong community engagement. Additionally, the village has capitalized on opportunities such as increasing demand for sustainable and eco-friendly tourism experiences. However, the research also identifies certain weaknesses and threats that need to be addressed, including limited infrastructure, inadequate marketing efforts, and competition from neighboring tourism destinations. Based on the SWOT analysis, this article proposes strategic recommendations to further enhance the branding strategy of Undisan Rural Tourism. These include improving infrastructure and facilities, expanding marketing efforts through digital platforms, fostering partnerships with local stakeholders, and implementing sustainable practices to preserve the environment. The study concludes that Undisan Rural Tourism's success in winning the 3rd Places of Tourism Village Award can be attributed to its unique branding strategy, which highlights the village's distinctive characteristics and eco-experiences. By addressing the identified weaknesses and capitalizing on existing strengths and opportunities, Undisan Rural Tourism can continue to thrive as a leading destination for sustainable rural tourism, setting an example for other tourism villages in the region